2015
DOI: 10.1371/journal.pone.0122580
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated Roles of the Inferior Frontal Gyrus and Superior Temporal Sulcus in Audiovisual Processing: Top-Down and Bottom-Up Mismatch Detection

Abstract: Visual inputs can distort auditory perception, and accurate auditory processing requires the ability to detect and ignore visual input that is simultaneous and incongruent with auditory information. However, the neural basis of this auditory selection from audiovisual information is unknown, whereas integration process of audiovisual inputs is intensively researched. Here, we tested the hypothesis that the inferior frontal gyrus (IFG) and superior temporal sulcus (STS) are involved in top-down and bottom-up pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…In general, HG band responses were enhanced compared to baseline and LF responses were decreased compared to baseline and the dynamic visual speech information increased the HG response and reduced the LF response (enhanced decrease). Enhanced HG band responses and decreased LF responses compared to baseline have been previously reported to audiovisual speech with ECoG (Rhone et al, 2016;Schepers et al, 2015;Uno et al, 2015) and seem to be a general response profile in population electrophysiological responses to sensory stimulation (e.g., Scheeringa, Koopmans, van Mourik, Jensen, & Norris, 2016;Siegel, Donner, Oostenveld, Fries, & Engel, 2008). Magnitude changes in neural brain responses reported here, particularly in the broad HG range, which has been linked to neuronal spiking activity (Ray & Maunsell, 2011), might underlie BOLD response changes seen in previous fMRI studies (Mukamel et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
“…In general, HG band responses were enhanced compared to baseline and LF responses were decreased compared to baseline and the dynamic visual speech information increased the HG response and reduced the LF response (enhanced decrease). Enhanced HG band responses and decreased LF responses compared to baseline have been previously reported to audiovisual speech with ECoG (Rhone et al, 2016;Schepers et al, 2015;Uno et al, 2015) and seem to be a general response profile in population electrophysiological responses to sensory stimulation (e.g., Scheeringa, Koopmans, van Mourik, Jensen, & Norris, 2016;Siegel, Donner, Oostenveld, Fries, & Engel, 2008). Magnitude changes in neural brain responses reported here, particularly in the broad HG range, which has been linked to neuronal spiking activity (Ray & Maunsell, 2011), might underlie BOLD response changes seen in previous fMRI studies (Mukamel et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
“…Cross-modal visual and auditory attention and their underlying neural characteristics have been extensively studied. Recent studies show that the modulation of both amplitude and phase of EEG oscillation could be important mechanisms to enable cross-modal interactions [ 7 9 ]. In addition, a recent EEG and fMRI study showed that when there is competition between visual and auditory stimuli, requiring active endogenous control of attention, there is modulation of activity within the sensory cortices, sensorimotor areas and the default mode network (DMN) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The account primarily assumes the involvement of the multimodal or motor-related areas 16,29,30,44 . Indeed, the regions implicated in this account in the current study (i.e., the right TPJ, SMA, bilateral IFG, and left temporal pole) have been reported to show contingency-error responses across multiple sensory modalities 12,18,26,27,4549 . Specifically, activation in the bilateral IFG has been implicated in sustained attention as part of the frontoparietal network 26,50 , while activation in the right SMA has been implicated in the planning of movement, motor intentions, and motor preparation 5153 , and activation in the right TPJ in the detection of action-contingency error 21,24,26,54 .…”
Section: Discussionmentioning
confidence: 55%